A biomolecular perspective on mobile pastoralism and its role in wider socioeconomic connections in the Chalcolithic South Caucasus - Mariya Antonosyan; Gwendoline Maurer; Satenik Mkrtchyan; Kseniia Boxleitner; Mariam Saribekyan; Anahit Hovhannisyan; Laura Furquim; Freg Stokes; Ruben Davtyan; Arsen Bobokhyan; Karen Azatyan; Jana Ilgner; et al. (iScience)
Summary: Mobile pastoralism is widely evoked when discussing technological developments, resource procurement, trans-regional interactions, and exchange networks in the South Caucasus. In this study, we conduct a comprehensive multiproxy investigation of faunal and botanical remains from the Middle to Late Chalcolithic in southern Armenia, at the high altitude Yeghegis-1 site, to directly assess herd mobility and human subsistence practices. Our findings indicate that, alongside intensified interregional connectivity, the inhabitants practiced a rather sedentary form of multi-resource pastoralism, while maintaining herds at the site year-round. These results complement and expand upon models of pastoral mobility and its perceived crucial role in sustaining inter- and intra-regional connectivity. We argue that alternative models of increased intra-regional connectivity, focused on exchange between different specialized settled economies, need to be considered and further research is essential to unravel the complex interplay between subsistence, trade, and socio-economic dynamics.